Geospatial Analyses of Earth Observation (EO) data - Pepe, Antonio; Zhao, Qing (IntechOpen, 2019)
Earth Observation and Geospatial Analysis presents current research related to the observation of Earth with sensors operating at various wavelengths. The book describes the use of remote sensing technologies for detecting and monitoring Earth's environmental changes (including surface and atmosphere) and its modifications over time. Chapters cover different research aspects in the framework of remote sensing with a particular emphasis on the use of hyperspectral and optical imageries. The presented experiments concern the study of soil properties, the analysis of land use/land changes, the analysis of bio-aerosols as well as the color of water, the investigation of the scar and samples of a cosmic meteoritic impact, and the theoretical treatment of the operation of spatial coordinate transformation in noisy environments. Overall, this book provides an overview of the adopted methodologies for the accomplishment of geospatial analyses to identify environmental changes due to climate change and natural phenomena.